Reliability-First Architecture for Large-Scale Batch Data Pipelines - Akanksha Mishra (International Journal of Computational and Experimental Science and Engineering, 2026)
Massive data processing systems that process data at billions of records at a time have inherent challenges in which correctness and reliability are more important than computational throughput. The reality of operations shows that instances of data quality take up a significant amount of organizational resources by taking up time in different detection stages and prolong the resolution process, which leads to cascading failures that disseminate through the downstream analytic systems. Distributed computing systems bring with them intrinsic failure modes such as the repetition of tasks via the retry mechanism, speculative execution of tasks, partial output values after multipart object storage write requests, and temporal inconsistency as part of historical reprocessing actions. The solution to these reliability issues involves architectural patterns to convert distributed uncertainty to deterministic recovery by explicit idempotency guarantees with coordination stores, transactional commit protocols where multi-object outputs are atomically published, date-scoped dependency graphs yielding temporal consistency in the process of backfills, and checkpoint-based recovery mechanisms that limit the reprocessing window. Configuration parameters that are standard to an industry, such as those provided by Apache Spark and Apache Airflow, directly determine the operational risk profile, such as settings related to the number of attempts to make on retries, speculation levels, concurrency levels, and state retention policies. The patterns of architecture shown in it set up the principles of reliability-first design, in which failures are non-destructive incidents, as opposed to disastrous. Strategies of implementation exploit coordination structures with transaction boundaries, orchestration structures with definite concurrency envelopes, and streaming structures with retention checkpoints to establish pipelines, which fail gracefully and guarantee correctness. These methods move the engineering capacity of engineering response to the engineering productive feature development by making reprocessing operations yield deterministic results consistent with the original execution semantics.